Phenotypic Heterogeneity of Cancer Associated Fibroblasts in Cervical Cancer Progression: FAP as a Central Activation Marker - Lesly Jazmin Bueno-Urquiza; Marisol Godínez-Rubí; Julio César Villegas-Pineda; Alejandra Natali Vega-Magaña; Luis Felipe Jave-Suárez; Ana Graciela Puebla-Mora; Gloria Estefanía Aguirre-Sandoval; María Guadalupe Martínez-Silva; Adrián Ramírez-de-Arellano; Ana Laura Pereira-Suárez (Cells, 2024)
Cervical cancer (CC) is the fourth leading cancer among women and is one of the principal gynecological malignancies. In the tumor microenvironment, cancer-associated fibroblasts (CAFs) play a crucial role during malignant progression, exhibiting a variety of heterogeneous phenotypes. CAFs express phenotypic markers like fibroblast activation protein (FAP), vimentin, S100A4, α-smooth muscle actin (αSMA), and functional markers such as MMP9. This study aimed to evaluate the protein expression of vimentin, S100A4, αSMA, FAP, and MMP9 in mesenchymal stem cells (MSC)-CAF cells, as well as in cervical cancer samples. MSC cells were stimulated with HeLa and SiHa tumor cell supernatants, followed by protein evaluation and cytokine profile to confirm differentiation towards a CAF phenotype. In addition, automated immunohistochemistry (IHQa) was performed to evaluate the expression of these proteins in CC samples at different stages. Our findings revealed a high expression of FAP in stimulated MSC cells, accompanied by the secretion of pro/anti-inflammatory cytokines. In the other hand, CC samples were observed to have high expression of FAP, vimentin, αSMA, and MMP9. Most importantly, there was a high expression of their activation proteins αSMA and FAP during the different stages. In the early stages, a myofibroblast-like phenotype (CAFs αSMA+ FAP+), and in the late stages a protumoral phenotype (CAF αSMA− FAP+). In summary, FAP has a crucial role in the activation of CAFs during cervical cancer progression.